2019
DOI: 10.21203/rs.2.18871/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of preoperative biliary drainage in patients with moderately severe obstructive jaundice on the outcomes of pancreatoduodenectomy: A meta-analysis study

Abstract: Background The purpose of this meta-analysis was to examine the impact of preoperative biliary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Elevated serum TBIL concentrations may indicate obstruction of the biliary tract. When bilirubin excretion is blocked, it may lead to liver insu ciency, nutrient metabolism disorders, an increase in bile duct pressure, and abnormal platelet production [29]. In addition, animal experiments have shown that biliary obstruction may also lead to increased levels of serum in ammatory cytokines and endotoxins, intestinal ora disorders, and intestinal mucosal barrier damage [30].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum TBIL concentrations may indicate obstruction of the biliary tract. When bilirubin excretion is blocked, it may lead to liver insu ciency, nutrient metabolism disorders, an increase in bile duct pressure, and abnormal platelet production [29]. In addition, animal experiments have shown that biliary obstruction may also lead to increased levels of serum in ammatory cytokines and endotoxins, intestinal ora disorders, and intestinal mucosal barrier damage [30].…”
Section: Discussionmentioning
confidence: 99%